Performance of lentil varities as influenced by different Rhizobium innoculations (Bangladesh Agronomy Journal, 2015)
A field experiment was conducted at the farm of Bangladesh Agricultural University, Mymensingh during November 2009 to March 2010 to study the response of three lentil varieties (viz., BARI Masur-1, BARI Masur-2 and BARI Masur-3) to Rhizobium inoculations to yield. There were three Rhizobium inoculants (Rhizobium strain BINA L4, Rhizobium strain TAL 640, and mixed culture) with uninoculated control and urea @ 50 kg ha-1. Phosphorus and potassium @ 26 kg P ha-1from TSP and 33 kg K ha-1 from MP were used as basal. It was observed that Rhizobium inoculation alone increased plant height, grain yield and crop residues yield of plant significantly compared to uninoculated control. Local inoculants BINA L4 performed better than the exotic culture TAL 640 in respect of yield. 50 kg urea ha-1 also recorded better results than control but not superior to any of the inoculation treatments. The highest seed (1,565 kg ha-1) and crop residue yields (3,303 kg ha-1) were recorded from the lentil variety BARIMasur-3 inoculated with mixed culture.Bangladesh Agron. J. 2014, 17(1): 41-46